Existence results for (p1; ... ; pn)-biharmonic systems under Navier boundary conditions - DOUMATE, TELE JONAS; Toyou, Robert L.; LEADI, LIAMIDI ARÈMOU (My University, 2022)
The authors study the existence of weak solutions for a (p1;...;pn)-biharmonic system via mountain pass theorem and establish semitrivial principal and strictly principal eigenvalues, positivity and simplicity results
Keywords: Nonlinear eigenvalue problems; Variational methods; (p1; ...; pn)-biharmonic systems; Boundary value; problems.